PENGARUH RETURN ON ASSET, LEVERAGE, UKURAN PERUSAHAAN KOMPENSASI RUGI FISKAL, KEPEMILIKAN INSTITUSIONAL, DAN KONEKSI POLITIK TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2015) - Fadila, Melisa; ', M. Rasuli; ', Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to analyze the influence of return on asset, leverage, company size, compensation tax losses, institutional ownership and political connections to tax avoidance. The populations in this research are manufacturing companies listed on the Indonesia stock exchange in 2011-2015. Sampling was done using purposive sampling method, based on data collection there are 44 manufacturing companies with 220 observations during five years. Analysis data method that is used on this research is multiple regressions using SPSS version 19.0. The result showed that return on asset have influence to tax avoidance, with t-count 4.257, t-table 1.971 and significance 0.05. Leverage have not influence to tax avoidance,with t-count 0.091, t-table 1.971 and significance 0.928. Company size has influence to tax avoidance, with t-count 2.505, t-table 1.971 and significance 0.05. Compensation tax losses have influence to tax avoidance, with t-count 3.965, t-table 1.971 and significance 0.05. Institutional ownership has influence to tax avoidance, with t-count 2.028, t-table 1.971 and significance 0.05. Political connections have not influence to tax avoidance, with t-count 1.461, t-table 1.971 and significance 0.145.Keyword : Tax Avoidance, ROA, Company Size, Compensation tax Losses, and Political Connections.